Image segmentation using a hybrid clustering technique and mean shift for automated detection acute leukaemia blood cells images - Jabar F.H.A.; Salam R.A.; Hassan R.; Waidah Ismail (Asian Research Publishing Network, 2024)
Indexed by Scopus